Efficacy of Punica granatum L. and Matricaria chamomilla L. herbal extracts on wound healing - Polat, Eren; Ates, Asiye Ozlem; Ozkan, Ahmet Selim; Kaya, Emre; Ozoner, Ozgur; Pekince-Ozoner, Merve; Serin, Hakan (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
Dermal injuries, which account for a significant portion of healthcare expenditures globally, occur in various forms due to the influence of various etiological factors, primarily trauma. For all these reasons, wound healing is among the most researched topics worldwide. This study aimed to investigate the effects of ointments obtained from Punica granatum L. (pomegranate) and Matricaria chamomilla L. (chamomile) extracts on secondary wound healing. 42 Sprague Dawley rats were used in the study. In the study, a total of six experimental groups were formed, each consisting of 7 rats: control group, healthy control group, Punica granatum treatment group, Matricaria chamomilla treatment group, Punica granatum and Matricaria chamomilla combination group (Punica granatumtreatment + Matricaria chamomilla treatment), and the group receiving an application containing olive oil, beeswax, and natural vitamin E. An excisional wound model was created using a biopsy punch on the back of the subjects in all groups except the healthy control group. While ointments prepared from herbal extracts were applied to the rats in the Punica granatum treatment, Punica granatum treatment + Matricaria chamomilla treatment, and Matricaria chamomilla treatment groups, rats in the control group received 0.9 % NaCl, and rats in the olive oil, beeswax, and natural vitamin E group were treated with a mixture of olive oil, beeswax, and vitamin E without any herbal extracts. At the end of the study, it was determined that the Matricaria chamomilla treatment group had the highest mean in terms of wound closure percentage and wound perimeter change percentage, while the Punica granatum treatment group had the lowest mean (P < 0.05). Although the best groups in terms of histopathological scoring were the Punica granatum treatment and Matricaria chamomilla treatment groups, no statistical difference was observed between the groups (P > 0.05). In terms of oxidative stress parameters (except for superoxide dismutase), the treatment groups were statistically significantly closer to the healthy control group than to the control group. Considering all evaluation criteria, it was concluded that Matricaria chamomilla plant was more effective on wound healing than Punica granatum plant and was a more suitable option for clinical use.
Eficacia de los extractos herbales de Punica granatum L. y Matricaria chamomilla L. en la cicatrización de heridas
Keywords: Wound healing; Matricaria chamomilla; Punica granatum; rat; excisional wound model